Cover Picture: Optochemical Control of Therapeutic Agents through Photocatalyzed Isomerization (Angew. Chem. Int. Ed. 28/2022). Issue 28 (9th June 2022) - Watson, Emma E.; Russo, Francesco; Moreau, Dimitri; Winssinger, Nicolas
Abstract : The photocatalyzed uphill isomerization of drugs using Ru(bpy3 )2 is reported by Nicolas Winssinger et al. in their Research Article (e202203390 ). This chemistry was shown to locally convert inactive drugs into active ones that alter the tubulin dynamics in cells (green structures in the background of the picture).